Early-stage photodegradation of aromatic poly(urethane-urea) elastomers. (November 2018) - Zhang, Tianlong; Xie, Fengwei; Motuzas, Julius; Bryant, Peter; Kurusingal, Valsala; Colwell, John M.; Laycock, Bronwyn
Abstract: The photooxidative stability of an aromatic segmented poly(urethane-urea) (PUU) elastomer, stabilised with a range of carbon black fillers, was assessed after very low UVA doses as a means to identify components that are highly susceptible to UV degradation, and suggest better design of such materials. Fourier-transform infrared (FTIR) analysis indicated rapid degradation of the urea bonds in the hard segments, followed by chain scission and photo-Fries reaction of the urethane linkages. In the soft segments, the oxidation of the original ether groups resulted in the formation of large amounts of ester groups, while some crosslinking of the ether groups was also evident. Carbon black provided moderate protection against degradation, with the smallest-sized particles being the most effective. Protection was evidenced by reduced surface cracking as well as an increased resistance to chemical changes in both the soft segments and hard segments. Even so, significant degradation was still evident at low UV doses suggesting that further stabilisation is required to increase the UV durability of these elastomers and improve their long-term performance. Graphical abstract: Highlights: Initial (60 h) photodegradation pathways of poly(urethane-urea) (PUU) was studied. Urea groups were the most UV-sensitive, followed by aliphatic ether groups. Carbon black provided moderate UV protection especially for aliphatic ether groups. The smallest-sized carbon black protected PUU against degradation more effectively. UV degradation-induced changes predominantly occurred at the surface.